Scaffolding transitions of possibility: the food walk as embodied method in Singapore. Issue Volume 14:Issues 3(2021) (3rd July 2021) - Ng, Huiying
ABSTRACT: Resilient food infrastructures responsive to instability and change often form at the urban edge of food systems. As such, they could take heed of knowledge practices that occur at the urban edge. This paper conceptualizes learning as a co-productive activity that can be scaffolded by space, and examines how it applies to the re-imagination of food systems. By considering walking as a method in the design of desired foodscapes, this paper addresses how "time niches" foster embodied knowledges of care and haptic connection. The two cases that illustrate this – a set of walking workshops with Singapore-based participants and a visualising workshop with visiting conference participants – consider how so-called lay and expert knowledges may come together in knowledge co-production in future-making practices. The paper explores how civic and decolonial practices occur in the sustainability transition of food.